Cover Feature: Tuning the C2/C1 Hydrocarbon Separation Performance in a BioMOF by Surface Functionalization (Eur. J. Inorg. Chem. 39‐40/2019). Issue 39 (23rd September 2019) - Huang, Yong‐Liang; Qiu, Pei‐Li; Zeng, Heng; Liu, Huan; Luo, Dong; Li, Yan Yan; Lu, Weigang; Li, Dan
Abstract : The Cover Feature shows how our BioMOF material can adsorb and separate different gases as freely as a dragon rides the waves, a legendary creature in Chinese mythology living in the sea and controlling the climate on the planet. The additional amine groups pointing toward the cavity on the channel surface are equivalent to the ball in the dragon‐s mouth. Amine introduction enhances the C2/C1 hydrocarbon separation performance of the material, just like the dragon ball increases a dragon‐s power of climate control. More information can be found in the Full Paper by W. Lu,  D. Li et al .